Supplementation of Cinnamon Extract Cinnamomum burmani in Commercial Feed on The Performance of Digestibility and Growth of Pacific White Shrimp Litopenaeus vannamei - Indariyanti, Nur; Hartono, Dwi Puji; Noor, Nuning Mahmudah (ABEC Indonesia, 2024)
Pacific white shrimp Litopenaus vannamei is one of the fishery export commodities. The problem with vanameshrimp cultivation in Indonesia is the high price of feed. One natural and environmentally friendly ingredient that canincrease feed efficiency and growth of vaname shrimp is Cinnamomum burmani. The active ingredient cinnamaldehydecontent in cinnamon can increase the utilization of carbohydrates as an energy source. This research aims to obtain the bestdose of cinnamon extract for digestibility, growth, and survival of vaname shrimp. The experimental design used aCompletely Randomized Design (CRD) consisting of 5 cinnamon extract treatment doses (0 ml/kg, 1 ml/kg, 2 ml/kg, 3ml/kg, and 4 ml/kg). The container used is an aquarium measuring 60 cm × 40 cm × 40 cm and filled with seawater. Thesize of the vaname shrimp used is ±2.5 g. The results showed that the performance parameters of digestibility, growth, andsurvival of shrimp fed with cinnamon extract showed significantly different results (p<0.05). The best dose of cinnamonextract was 3 ml/kg feed.